2012
DOI: 10.1111/mmi.12044
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of enterotoxigenic Escherichia coli colonization factor CS6 reveals a novel type of functional assembly

Abstract: SummaryColi surface antigen 6 (CS6) is a widely expressed enterotoxigenic Escherichia coli (ETEC) colonization factor that mediates bacterial attachment to the small intestinal epithelium. CS6 is a polymer of two protein subunits CssA and CssB, which are secreted and assembled on the cell surface via the CssC/CssD chaperone usher (CU) pathway. Here, we present an atomic resolution model for the structure of CS6 based on the results of X-ray crystallographic, spectroscopic and biochemical studies, and suggest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…The stoichiometry of oligomers was not disrupted even in a less polar solvent, like 50% ethylene glycol. We did not find either homooligomers or hetero-oligomers in unequal stoichiometry, as documented by Roy et al (2012). This hetero-oligomeric assembly as a function of increasing protein concentration…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…The stoichiometry of oligomers was not disrupted even in a less polar solvent, like 50% ethylene glycol. We did not find either homooligomers or hetero-oligomers in unequal stoichiometry, as documented by Roy et al (2012). This hetero-oligomeric assembly as a function of increasing protein concentration…”
Section: Discussionmentioning
confidence: 61%
“…The structural analysis showed that both the subunits of CS6 are mostly rich in b-sheets (Roy et al, 2012). We found that the CS6 protomers interact with each other through these b-sheets during oligomerization, by noncovalent interactions.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, the N termini of both subunits showed the presence of a donor strand (G d ) motif characterized by alternating hydrophobic and hydrophilic residues (10). The C termini of CssA and CssB showed the presence of a chaperone protein recognition motif, as defined for P pilus structural subunits.…”
mentioning
confidence: 99%